Separation with Determination Iron (III) and Paracetamol Drug via Onium System - Safa S. Zayied (Journal of Global Pharma Technology, 2019)
Onium technique used as sensitive method for extraction and determination Fe(III) by using paracetamol drug so determination this drug by using Fe(III) within a study for determination the optimum conditions appear onium species formed wave length for maximum absorbance is equal to λ max =247nm,  so this formation for stable onium species need existence 1.5 M HCl in aqueous solution and 1x10-4M paracetamol, with 15 minutes shaking time, also and in order to enhancement the extraction efficiency need operation existence 50% methanol and 0.1 M NaCl in the aqueous phase thermodynamic study shows the operation was endothermic with data equal to Δ Hex = 0. 0397  KJmol-1 , Δ G ex = -54.44 kJmol-1, Δ Sex =174.06 J mol-1k-1 , the study involved also organic solvent effect , interference and spectrophotometric determination of Fe3+ and drug paracetamol.Key words: Onium System, Iron (III), Paracetamol, Determination.